2017
DOI: 10.1097/md.0000000000008663
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic adjacent segment disease after single-lever anterior cervical discectomy and fusion

Abstract: The purpose of this study was to determine the incidence and risk factors of symptomatic adjacent segment disease (ASD) following single-lever anterior cervical discectomy and fusion (ACDF) for cervical degenerative diseases.From January 2000 to December 2010, a total of 582 patients with cervical radiculopathy and myelopathy who had undergone single-lever ACDF surgery in the authors’ institution were reviewed retrospectively. Patients who had a revision surgery for symptomatic ASD were selected for this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…This is because patients presenting for ASD from previous ACDF will be older, have established degeneration already by definition, and have previous surgical disruption to surrounding soft tissue, which are all proven risk factors for ASD itself. 26-28 Thus, perhaps the significant differentiator between ACDF and TDR to manage ASD is the long-term success of each procedure in preventing further ASD. Only time will tell if such a superiority exists, as currently the literature is too young to evaluate this, and this will undoubtedly assist clinicians in determining the optimal approach for a patient.…”
Section: Discussionmentioning
confidence: 99%
“…This is because patients presenting for ASD from previous ACDF will be older, have established degeneration already by definition, and have previous surgical disruption to surrounding soft tissue, which are all proven risk factors for ASD itself. 26-28 Thus, perhaps the significant differentiator between ACDF and TDR to manage ASD is the long-term success of each procedure in preventing further ASD. Only time will tell if such a superiority exists, as currently the literature is too young to evaluate this, and this will undoubtedly assist clinicians in determining the optimal approach for a patient.…”
Section: Discussionmentioning
confidence: 99%
“…Baba et al 26 assessed >100 patients undergoing anterior cervical fusion for cervical myelopathy with an average follow-up of 8.5 years, and 25% of these patients subsequently developed new spinal canal stenosis on the adjacent fused segments. In a retrospective study, Wang et al 27 showed that 6.2% of patients undergoing single-segment ACDF developed adjacent segment disease. In the present study, ASD was observed in only 22 (19.5%) patients at the final follow-up, but its occurrence was not associated with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have found predictors of CASP to be age over 50 years at the time of surgery, developmental canal stenosis, preoperative degeneration of adjacent segments, and postoperative imbalance of sagittal alignment. 8,9 Whereas RASP and CASP have been widely reported in the literature, the hypothesis that a correlation exists between them remains unproven. Often publications include the results of both RASP and CASP rates within the studied population, but attempted correlation is not reported.…”
Section: Introductionmentioning
confidence: 99%